Freaks of a feather : a marine grunt's memoir - Tellessen, Kacy (Latah Books, 2021)
Kacy Tellessen is a grunt. After completing high school in rural Washington, he enlisted in the Marine Corps and began the hero's journey he imagined might parallel those epic tales he'd consumed throughout adolescence. But what Tellessen lived through--from boot camp to the battlefield and home again--had little in common with Homer's tales or Hollywood's depictions. In his memoir, Tellessen offers a truer account of life as an infantryman: the complicated, conflicting, adrenaline-pumping, and traumatic experience of war. Though much of our country's fighting and dying is done by infantry members, few accounts detail the grunt experience with as much clarity and vulnerability as Freaks of a Feather. Kacy was born in Spokane and raised in Spangle, Washington, a small farming community that clings to the edge of the Palouse. Kacy joined the Marine Corps infantry directly out of high school and deployed twice to Iraq as an Infantry machine gunner with Second Battalion, Third Marines from 2005-2009. His work has appeared in The New York Times, Zero-Dark-Thirty literary journal, as well as the SOFLETE website.